Enhanced Recent Local Moisture Recycling on the Northwestern Tibetan Plateau Deduced From Ice Core Deuterium Excess Records. Issue 23 (5th December 2017) - An, Wenling; Hou, Shugui; Zhang, Qiong; Zhang, Wangbin; Wu, Shuangye; Xu, Hao; Pang, Hongxi; Wang, Yetang; Liu, Yaping
Abstract: Local moisture recycling plays an essential role in maintaining an active hydrological cycle of the Tibetan Plateau (TP). Previous studies were largely limited to the seasonal time scale due to short and sparse observations, especially for the northwestern TP. In this study, we used a two‐component mixing model to estimate local moisture recycling over the past decades from the deuterium excess records of two ice cores (i.e., Chongce and Zangser Kangri) from the northwestern TP. The results show that on average almost half of the precipitation on the northwestern TP is provided by local moisture recycling. In addition, the local moisture recycling ratio has increased evidently on the northwestern TP, suggesting an enhanced hydrological cycle. This recent increase could be due to the climatic and environmental changes on the TP in the past decades. Rapid increases in temperature and precipitation have enhanced evaporation. Changes of land surface of plateau have significantly increased evapotranspiration. All of these have intensified local moisture recycling. However, the mixing model used in this study only includes a limited number of climate factors. Some of the extreme values of moisture recycling ratio could be caused by large‐scale atmospheric circulation and other climatic and weather events. Moreover, the potential mechanisms for the increase in local recycling need to be further examined, since the numeric simulations from climate models did not reproduce the increased contribution of local moisture recycling in precipitation. Key Points: The local moisture recycling ratios were estimated for the northwestern Tibetan Plateau over the past decades The local moisture recycling contributes close to half of the regional precipitation The local moisture recycling has enhanced in recent decades, and this may be related to changes of regional climate, environment conditions